H1 but not H2 histamine antagonist receptors mediate anxiety-related behaviors and emotional memory deficit in mice subjected to elevated plus-maze testing - Serafim,K.R. (2013)
This study investigated the role of H1 and H2 receptors in anxiety and the retrieval of emotional memory using a Trial 1/Trial 2 (T1/T2) protocol in an elevated plus-maze (EPM). Tests were performed on 2 consecutive days, designated T1 and T2. Before T1, the mice received intraperitoneal injections of saline (SAL), 20 mg/kg zolantidine (ZOL, an H2receptor antagonist), or 8.0 or 16 mg/kg chlorpheniramine (CPA, an H1 receptor antagonist). After 40 min, they were subjected to the EPM test. In T2 (24 h later), each group was subdivided into two additional groups, and the animals from each group were re-injected with SAL or one of the drugs. In T1, the Student t-test showed no difference between the SAL and ZOL or 8 mg/kg CPA groups with respect to the percentages of open arm entries (%OAE) and open arm time (%OAT). However, administration of CPA at the highest dose of 16 mg/kg decreased %OAE and %OAT, but not locomotor activity, indicating anxiogenic-like behavior. Emotional memory, as revealed by a reduction in open arm exploration between the two trials, was observed in all experimental groups, indicating that ZOL and 8 mg/kg CPA did not affect emotional memory, whereas CPA at the highest dose affected acquisition and consolidation, but not retrieval of memory. Taken together, these results suggest that H1 receptor, but not H2, is implicated in anxiety-like behavior and in emotional memory acquisition and consolidation deficits in mice subjected to EPM testing.